A prospective randomized trial of trans cervical Foley’s with extra amniotic saline infusion versus intra cervical prostaglandin E2 gel for induction of labour setting - Kumar, Sunil; D., Rita; Desai, R. M.; K. R., Mohan Kumar; ., Dhanalaxmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study evaluated the effectiveness of Extra-amniotic saline infusion (EASI) in comparison with that of intracervical Prostaglandin E2 (PGE2) gel for cervical ripening and induction of labour. Methods: The study conducted in SDM College of Medical College Dharwad, Department of OBG, from December 2012 to November 2013. Consecutive patients with unfavorable cervices requiring pre-induction cervical ripening and induction of labour for various indications were asked to participate in this study. 50 patients (Group A) underwent extra amniotic saline infusion and 50 patients (Group B) underwent PGE2 gel application. Post induction augmentation if required was administered. Labour profile outcomes were compared between the groups. Results: Results were comparable in terms of maternal age, indication for induction in majority of cases, pre-induction Bishop Score, mode of delivery, complications and side effects, neonatal complications, and Apgar Score. The mean post induction Bishop Score was higher in EASI group by an average of 9. The mean duration of augmentation was more in PGE2 group by an average of 2 hrs. The induction delivery interval (IDI) was prolonged by an average of 3.5 hours in PGE2 group. Conclusions: For pre-induction cervical ripening the extra amniotic saline infusion is valid alternative for the PGE2 gel. Both the modes of induction were equally safe and effective in terms of mode of delivery and Apgar Score. EASI, however, had rapid cervical ripening and shorter induction delivery interval.